Development of nanostructures in the diagnosis of drug hypersensitivity reactions. Issue 4 (August 2016) - Mayorga, Cristobalina; Perez-Inestrosa, Ezequiel; Molina, Noemi; Montañez, Maria I.
Abstract : Purpose of review: This article provides an overview of novel nanoscale structures potentially applicable to the field of allergy, and to discuss the required properties, advantages, and disadvantages of those nanostructures for clinical application focusing on diagnosis of drug hypersensitivity reactions. Recent findings: Advances in the development of different nanostructures are favoring their biomedical applications. One area of interest is the interaction between nanostructures and the immune system, including their ability to emulate carrier molecules and their potential use for the diagnosis of allergic reactions. Summary: Immunoassays are the most widely used in-vitro test for evaluating immunoglobulin E (IgE)-mediated drug hypersensitivity reactions. However, they have important technical limitations affecting their sensitivity. A wide variety of nanostructures have been designed to quantify specific IgE, with the aim of diagnosing different kinds of allergies. Nanoparticles-based colloidal immunoassay employed in microdevices and/or miniaturized systems are improving IgE detection sensitivity. Dendrimers have shown immense potential for the design and development of sensor platforms for evaluating IgE-mediated drug hypersensitivity reactions, due to the increase in hapten density and IgE accessibility. In this sense, a variety of dendritic structures as well as their hybridization to different solid supports have been shown to be successful when applied in the diagnosis of drug allergy. Moreover, the knowledge of the complete antigenic determinants would allow their inclusion and therefore further improvement of the sensitivity.